2011
DOI: 10.1016/j.brat.2011.09.003
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility study of Acceptance and Commitment Therapy for emotional dysfunction following psychosis

Abstract: The experience of psychosis can lead to depression, anxiety and fear. Acceptance and Commitment Therapy (ACT) facilitates individuals to accept difficult mental experiences and behave in ways that are consistent with personally held values. This study was a single (rater) blind pilot randomised controlled trial of ACT for emotional dysfunction following psychosis.Twenty-seven participants with psychosis were randomised to either: ten sessions of ACT plus treatment as usual (TAU) or TAU alone. The Hospital Anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
139
0
6

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(154 citation statements)
references
References 38 publications
7
139
0
6
Order By: Relevance
“…Two reports were found that did not meet inclusion criteria for the systematic review, but referred to trials that targeted affective disturbance specifically in people with psychosis (White et al, 2011;Jackson et al, 2009), which most of the psychological therapy trials above had not set out explicitly to achieve. One further paper (Lecomte et al, 1999) reported on a trial of a self esteem therapy intervention that was similar to the four reviewed above (Hall & Tarrier, 2003;Knight, Wykes, & Hayward, 2006;Laithwaite et al, 2007;Laithwaite et al, 2009).…”
Section: Three Excluded Studies With Some Relevancementioning
confidence: 99%
See 4 more Smart Citations
“…Two reports were found that did not meet inclusion criteria for the systematic review, but referred to trials that targeted affective disturbance specifically in people with psychosis (White et al, 2011;Jackson et al, 2009), which most of the psychological therapy trials above had not set out explicitly to achieve. One further paper (Lecomte et al, 1999) reported on a trial of a self esteem therapy intervention that was similar to the four reviewed above (Hall & Tarrier, 2003;Knight, Wykes, & Hayward, 2006;Laithwaite et al, 2007;Laithwaite et al, 2009).…”
Section: Three Excluded Studies With Some Relevancementioning
confidence: 99%
“…One further paper (Lecomte et al, 1999) reported on a trial of a self esteem therapy intervention that was similar to the four reviewed above (Hall & Tarrier, 2003;Knight, Wykes, & Hayward, 2006;Laithwaite et al, 2007;Laithwaite et al, 2009). White et al (2011) reported on a randomised controlled trial of Acceptance and Commitment Therapy (ACT) for emotional dysfunction following psychosis, which was published too late to be included in the above study pool. 27 people with psychosis were randomised to ACT or treatment as usual (TAU).…”
Section: Three Excluded Studies With Some Relevancementioning
confidence: 99%
See 3 more Smart Citations